BF3·OEt2 mediated metal-free one-pot sequential multiple annulation cascade (SMAC) synthesis of complex and diverse tetrahydroisoquinoline fused hybrid molecules. Issue 12 (3rd March 2016) - Shinde, Anand H.; Vidyacharan, Shinde; Sharada, Duddu S.
Abstract : A highly efficient and distinct BF3 ·OEt2 mediated one-pot metal-free sequential multiple annulation cascade (SMAC) protocol for the synthesis of complex and diverse THIQ fused hybrid molecules has been presented. Abstract : A highly efficient and distinct BF3 ·OEt2 mediated metal-free SMAC protocol for the synthesis of complex and diverse hybrid molecules viz. indazole fused tetrahydroisoquinolinoquinoxalines, and tetrahydroisoquinolinodiazepine has been developed. The transformation is based on sequential cascade processes involving 2 H -indazole formation and deprotection Pictet–Spengler cyclization steps in one-pot fashion. The protocol demonstrates the utility of sequential multiple annulations in a cascade fashion. The present one-pot protocol uses the Solid State Melt Reaction (SSMR) strategy for the synthesis of the intermediate 2 H -indazole. The method is operationally simple and represents a new approach for C–C, three C–N and N–N bond formation with a wide substrate scope.